2012
DOI: 10.1212/wnl.0b013e31826e263d
|View full text |Cite
|
Sign up to set email alerts
|

Auditory threshold, phonologic demand, and incident dementia

Abstract: This study has found an association of auditory threshold with dementia and cognitive decline over a 17-year period. The mechanisms underlying this association are unclear and may include a prodromal effect of dementia on auditory threshold, an effect of auditory threshold on cognitive assessment, an effect of auditory threshold on cognitive loss, or a shared etiologic pathway between both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
242
6
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(263 citation statements)
references
References 34 publications
8
242
6
7
Order By: Relevance
“…The previous studies of objective hearing loss used a pure tone audiometry test, whereas the current study used self‐reported hearing measures in the longitudinal analyses 6, 7, 11. Nevertheless, a significant positive association was found between the self‐reported and objective test measure in Wave 7.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The previous studies of objective hearing loss used a pure tone audiometry test, whereas the current study used self‐reported hearing measures in the longitudinal analyses 6, 7, 11. Nevertheless, a significant positive association was found between the self‐reported and objective test measure in Wave 7.…”
Section: Discussioncontrasting
confidence: 59%
“…The current study built on previous longitudinal studies conducted in the United States and Wales that found that individuals with moderate and severe hearing loss were at greater risk of developing dementia 6, 7, 12, 22. Six hundred thirty‐nine adults aged 65 and older from the Baltimore Longitudinal Study of Aging were prospectively analysed over 11.9 years 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Hearing loss in older adults impairs verbal communication, contributes to social isolation, 2 and has been independently associated with poorer cognitive functioning [3][4][5] and incident dementia. [6][7] While hearing aids improve audibility for most individuals with mild to moderate hearing loss, those who suffer from severe to profound hearing loss generally may acquire greater benefit from electrical hearing provided by a cochlear implant (CI). 8 Currently, the number of older adults in the United States who would potentially meet audiologic criteria for a CI is approximately 150,000, 1 but less than 5% of these older adults are likely to have received a CI System.…”
Section: Introductionmentioning
confidence: 99%